2007
DOI: 10.1017/s0950268807009831
|View full text |Cite
|
Sign up to set email alerts
|

Performance of an interferon-gamma release assay for diagnosing latent tuberculosis infection in children

Abstract: Newly developed interferon-gamma release assays have become commercially available to detect tuberculosis (TB) infection in adults. However, little is known about their performance in children. We compared test results between the QuantiFERON-TB Gold test (QFT) and tuberculin skin test (TST) in young children living with pulmonary TB patients in Cambodia. Of 195 children tested with both QFT and TST, the TST-positive rate of 24% was significantly higher than the QFT-positive rate of 17%. The agreement between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
1
6

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 16 publications
4
48
1
6
Order By: Relevance
“…25 La sensibilidad que encontramos (25%) es inferior a la publicada (55%) por Machingaidze 10 en niños de regiones con alta incidencia de tuberculosis. Kampmann y sus colaboradores 26 señalaron una sensibilidad de 32% en niños vacunados o no con BCG.…”
Section: Qft-g ® Para El Diagnóstico De La Tuberculosis Latenteunclassified
See 1 more Smart Citation
“…25 La sensibilidad que encontramos (25%) es inferior a la publicada (55%) por Machingaidze 10 en niños de regiones con alta incidencia de tuberculosis. Kampmann y sus colaboradores 26 señalaron una sensibilidad de 32% en niños vacunados o no con BCG.…”
Section: Qft-g ® Para El Diagnóstico De La Tuberculosis Latenteunclassified
“…20 Contraria a su baja sensibilidad la prueba QFT-G ® mostró una excelente especificidad (98.6%), lo que es consistente con otros reportes pediá-tricos. 11,25,27 La especificidad del método para detectar tuberculosis latente sugiere que la prueba es útil para descartar la infección en niños; aunque los resultados deben ser interpretados cautelosamente ya que, ante la ausencia de un criterio de referencia apropiado para la forma latente y la escasez de estudios longitudinales, es difícil concluir acerca de su especificidad cuando se le compara con el derivado proteínico. 20 La capacidad mostrada por el QFT-G ® sugiere que su incorporación a los procedimientos diagnósticos empleados para descartar tuberculosis latente en niños tendría capacidad superior al derivado proteínico pues, entre otras cosas, no se ve afectado por las tasas de vacunación con BCG.…”
Section: Qft-g ® Para El Diagnóstico De La Tuberculosis Latenteunclassified
“…Furthermore, IGRA tests may be repeated, regardless of their previous results, unlike TST, which should only be repeated if previously negative. However, serial testing of subjects not undergoing treatment has indicated that there are high rates of spontaneous reversions and conversions, although it is always harder to know if conversion is spontaneous or a consequence of real TB infections (58,59). Nonspecific infections and vaccines, laboratorial technique variability (such as blood withdrawal preparation), delay to and time of incubation, and the kit being used are other possible explanations for a conversion.…”
Section: C) Highly Exposed Populations and Serial Testingmentioning
confidence: 99%
“…On comprend mieux les recommandations courantes quant à leur utilisation chez les enfants lorsqu'on tient compte de ces limites. En bref, dans les milieux où l'incidence de TB est faible, le point de vue général est que les tests sont plus spécifiques et ont une meilleure corrélation avec les gradients d'exposition aux cas de référence contagieux que l'IDR (18)(19)(20)(21). Cependant, cette évaluation est entravée par l'absence de norme de référence pour diagnostiquer la TBIL et l'absence de données longitudinales pour valider la valeur prédictive des TDIG par rapport à l'IDR.…”
Section: Le Rôle Des Tdig Chez Les Enfantsunclassified
“…Cependant, cette évaluation est entravée par l'absence de norme de référence pour diagnostiquer la TBIL et l'absence de données longitudinales pour valider la valeur prédictive des TDIG par rapport à l'IDR. La concordance générale entre l'IDR et le TDIG pour diagnostiquer la TBIL chez les enfants semble se situer entre 55 % et 95 % (18)(19)(20)22,23) …”
Section: Le Rôle Des Tdig Chez Les Enfantsunclassified